2004
DOI: 10.1002/chin.200444225
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase‐Inhibiting New Steroidal Alkaloids from Sarcococca hookeriana of Nepalese Origin.

Abstract: Bioassay-guided phytochemical investigation of Sarcococca hookeriana has resulted in the isolation and structure elucidation of five new pregnane-type steroidal alkaloids: (À)-hookerianamide A ( (2b,3b,4b,20S)-pregn-14-ene; 4), and ()-phulchowkiamide A ( (3b,20S)-20-(methylamino)-3-[(2-methylbut-2-enoyl)amino]-5a-pregn-2-en-4-one; 5). These compounds, as well as the two chemically derived acetyl derivatives 6 and 7, displayed cholinesterase inhibition in a concentration-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…[84] Several Sarcococca steroidal alkaloids have been reported to have anticholinesterase activity, with IC50 values in the range of 0.5-249 mm for AChE, (+)phulchowkiamide A being the most active, while for BChE the IC50 varies from 0.3 to 200 mm, hookerianamide I possessing the lowest IC50 value (see Table S1). [85][86][87][88][89][90][91][92][93][94][95] Through Lineweaver-Burk and Dixon plots, Khalid et al [84] demonstrated that the majority of the pregnane-type alkaloids obtained from Sarcococca saligna have a pure noncompetitive type of inhibition for both cholinesterases.…”
Section: Classes Of Anticholinesterase Alkaloids Steroidal and Tritermentioning
confidence: 99%
“…[84] Several Sarcococca steroidal alkaloids have been reported to have anticholinesterase activity, with IC50 values in the range of 0.5-249 mm for AChE, (+)phulchowkiamide A being the most active, while for BChE the IC50 varies from 0.3 to 200 mm, hookerianamide I possessing the lowest IC50 value (see Table S1). [85][86][87][88][89][90][91][92][93][94][95] Through Lineweaver-Burk and Dixon plots, Khalid et al [84] demonstrated that the majority of the pregnane-type alkaloids obtained from Sarcococca saligna have a pure noncompetitive type of inhibition for both cholinesterases.…”
Section: Classes Of Anticholinesterase Alkaloids Steroidal and Tritermentioning
confidence: 99%
“…They also exhibited inhibitory effects on drug transport and multidrug resistance in human cancer cells [2], and antileishmanial potential [3]. Four species, S. coriacea, S. saligna, S. hookerina, and S. wallichi are found in Nepal [4,5]. S. wallichi is widely distributed in central Nepal at altitudes above 2300 m [6].…”
mentioning
confidence: 99%
“…3054 (Table 2). In the 13 C NMR (Table 1) spectrum, twenty-four signals were observed. Thus, compound 1 was identified to be a pregnane-type steroidal alkaloid.…”
Section: Resultsmentioning
confidence: 99%
“…1). The known compounds isolated were characterized to be 11-hydroxyepipachysamine-E (4) [12], (2α, 3β, 4β, 20S)-2, 4-bis(acetoxy)-20-(N, N-dimethylamino)-3-[(3-methylbut-2-enoyl) amino]-5α-pregnane (5) [13], vagnine B (6) [14], (20S)-20-(N, N-dimethylamino)-3β-methoxy-pregn-5-ene (7) [15], (+)-irehine (8) [16], axillaridine A (9) [17], epi-pachysamine B (10) [14], salonine B (11) [18], funtumafrine C (12) [19], pachysamine M (13) [20], and hookerianamide B (14) [13] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation